Sequential optimization of a water-based polygeneration system in ethylene glycol production - Prihatin, T. (Institute of Physics Publishing, 2020)
Polygeneration system as one of the promising strategies shows the great potential for natural resource sustainability, particularly water. In this paper, a model of water-based polygeneration system to minimize the freshwater consumption and the wastewater generation is presented. Water usage in a heat and power utility, cooling utility, and chemical production are modelled simultaneously. To demonstrate the applicability of the model, a case study on the synthesis of optimum water-based polygeneration system is developed for an ethylene glycol production. A two-steps optimization method is presented. The first step consists of the synthesis and design of the polygeneration unit in which a superstructure containing three subsystems, i.e. heat and power generations, re-circulating cooling water system, and chemical production is introduced. A mixed integer non linear program (MINLP) model is developed to allow the selection of choices. The second step includes the incorporating of wastewater treatment strategy and a non linear program model is developed. As results, comparing to the simultaneous method in the same case study, this approach gives a better result in a computation efficiency. Â© 2020 Published under licence by IOP Publishing Ltd.